The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2003
DOI: 10.1227/01.neu.0000089481.87226.f7
|View full text |Cite
|
Sign up to set email alerts
|

Toward Optimal Tissue Sealants for Neurosurgery: Use of a Novel Hydrogel Sealant in a Canine Durotomy Repair Model

Abstract: The hydrogel-treated animals exhibited normal progression of dural healing, no dural adhesions, and no underlying effects on the brain. Although dural healing progressed normally, the control animals displayed marked peridural adhesions. The results of this in vivo study suggest that hydrogels, such as that used here, may significantly decrease cerebrospinal fluid leakage, thereby increasing the safety and effectiveness of dural closure in patients and facilitating surgical reexploration.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
77
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 98 publications
(84 citation statements)
references
References 53 publications
(60 reference statements)
7
77
0
Order By: Relevance
“…In addition, the material should also be thin in order not to create tension between dural edges. There were interesting reports pointing to prevention of adhesions in cranial or spinal epidural layer (3,4,6,13,20). In the present study, no fibrosis was observed in most of the samples of the Spongostan™ group and looser connective tissue dominates the field of study with irregularly arranged thin collagen fibers and fibroblasts.…”
Section: Discussionsupporting
confidence: 51%
“…In addition, the material should also be thin in order not to create tension between dural edges. There were interesting reports pointing to prevention of adhesions in cranial or spinal epidural layer (3,4,6,13,20). In the present study, no fibrosis was observed in most of the samples of the Spongostan™ group and looser connective tissue dominates the field of study with irregularly arranged thin collagen fibers and fibroblasts.…”
Section: Discussionsupporting
confidence: 51%
“…However, one of the drawbacks of using DuraSeal TM is its potential to swell up to 50% and its slow resorption rate. The peak expansion of DuraSeal TM was between 3 and 14 days postapplication in a dog model with complete resorption at 8 weeks [6,10]. Owing to these findings, we believe the application of DuraSeal TM in a confined bony area is contraindicated as a result of the concern of swelling and nerve root compression (DuraSeal TM product information.…”
Section: Discussionmentioning
confidence: 95%
“…2,3,[14][15][16] This hydrogel sealant system can also be used to seal dural defects. Polyethylene glycol hydrogel sealant is a chemical synthetic sealant formed by mixing PEG ester solution and trilysine amine solution.…”
mentioning
confidence: 99%